Primary antibiotic resistance and associated mechanisms in Helicobacter pylori isolates from Senegalese patients - Seck Abdoulaye; Burucoa Christophe; Dia Daouda; Mbengue Mouhamadou; Onambele Manuella; Raymond Josette; Breurec Sebastien (BMC, 2013)
Abstract Background Antibiotic combination therapy for Helicobacter pylori eradication must be adapted to local resistance patterns, but the epidemiology of H. pylori resistance to antibiotics is poorly documented in Africa. The aim was to determine the antibiotic resistance rates, as well as the associated molecular mechanisms, of strains isolated in Dakar, Senegal. Methods One hundred and eight H. pylori strains were isolated between 2007 and 2009 from 108 patients presenting with upper abdominal pain to the Gastroenterology Department of Le Dantec Hospital. Antimicrobial susceptibility testing was performed for amoxicillin, clarithromycin, metronidazole, levofloxacin and tetracyclin using the E-test method. Mutations in the 23S rRNA gene of clarithromycin-resistant strains and in gyrA and gyrB of levofloxacin-resistant strains were investigated. Results Isolates were characterized by no resistance to amoxicillin (0%), tetracycline (0%), and very low rate of resistance to clarithromycin (1%), but a high rate of resistance to metronidazole (85%). The clarithromycin-resistant strain displayed the A2143G mutation. A worrying rate of levofloxacin resistance was detected (15%). N87I and D91N were the most common mutations in the quinolone-resistance-determining region of gyrA. Conclusions The first-line empirical regimen for H. pylori eradication in Senegal should include clarithromycin. Increasing rates of fluoroquinolone resistance detected should discourage the use of levofloxacin-containing regimens without prior antimicrobial susceptibility testing.